2021
DOI: 10.3390/buildings11070289
|View full text |Cite
|
Sign up to set email alerts
|

Improving the IAQ for Learning Efficiency with Indoor Plants in University Classrooms in Ajman, United Arab Emirates

Abstract: The objective of this paper is to investigate the effect of improving indoor air quality with indoor plants. As a methodology, two target classrooms with the same size (120.64 m2) and 32 students per room were selected. Then, 48 areca palm pots (average leaf area of 300 cm2/pot) were placed, and the plant density was 14.68% of the floor area. Subjective assessment for general questions, learning motivation, perceived air quality, and SBS symptoms was conducted at 5 min after the class started and 5 min before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…The outdoor temperature was 23-24 ℃, so the indoor temperature was within comfort conditions as per mentioned by the (ISHARE). Few research studies mentioned data collection point one, readings were taken at the centre (Shree et al, 2019a;Shree et al, 2019b;Jung & Awad, 2021) or only two points depending upon occupancy and plant position (Kim et al, 2013;Han, 2019;2020) List of instruments used for experiments for different parameters mentioned the readings taken by moving the instrument around the room (Bhargava et al, 2021). Whereas the current study mentioned systematic arrangements of data collection points.…”
Section: Environmental Parameter Measurement Methodologymentioning
confidence: 78%
See 2 more Smart Citations
“…The outdoor temperature was 23-24 ℃, so the indoor temperature was within comfort conditions as per mentioned by the (ISHARE). Few research studies mentioned data collection point one, readings were taken at the centre (Shree et al, 2019a;Shree et al, 2019b;Jung & Awad, 2021) or only two points depending upon occupancy and plant position (Kim et al, 2013;Han, 2019;2020) List of instruments used for experiments for different parameters mentioned the readings taken by moving the instrument around the room (Bhargava et al, 2021). Whereas the current study mentioned systematic arrangements of data collection points.…”
Section: Environmental Parameter Measurement Methodologymentioning
confidence: 78%
“…Hence plants not only clean air by the process of photosynthesis and phytoremediation but also can control temperature and relative humidity which can control the airborne pollutants (Aini Jasmin et al, 2012a). Some studies showed that after placing the plants indoors CO 2 levels were increased and got stabilized (Jung & Awad, 2021;H. Kim et al, 2016;Smith & Pitt, 2011) whereas few studies noted a continuous decreasing trend (Bhargava et al, 2021;Pamonpol et al, 2020;Pegas et al, 2012).…”
Section: Benefits Of Indoor Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dubai Municipality regulates the IAQ (Indoor Air Quality) with the stipulation of less than 0.08 ppm (parts per million) of formaldehyde (CH 2 O), less than 300 micrograms/m 3 of TVOC (Total Volatile Organic Compound), and less than 150 micrograms/m 3 of TSP (Total Suspended Particles) (less than 10 microns) in 8 h of continuous monitoring prior to occupancy. In relation to this provision, there is a recommended standard for pollutants, but there is no compulsory regulation for non-conformity [68]. However, according to this new provision, the construction industry is desperately trying to reduce pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the indoor air environment in residential spaces is one of the most critical problems in Dubai (Al Qassimi and Jung, 2021). Factors affecting these indoor air environment problems include harmful chemicals such as formaldehyde (HCHO) and Volatile Organic Compounds (VOCs) such as Benzene (C 6 H 6 ), Toluene (C 7 H 8 ), Ethylbenzene (C 8 H 10 ), Xylene (C 8 H 10 ), and Styrene (C 8 H 8 ), emitted from building materials, furniture, home appliances, and indoor household items, airborne bacteria, fungus, and viruses Jung and Awad, 2021c). In addition, the causes are very diverse, such as problems with buildings and mechanical facilities, such as a decrease in the opening area due to the high-rise of a residential building, and a lack of ventilation due to high insulation and high airtightness for energy saving of buildings (Ai et al, 2015;Awad and Jung, 2021b).…”
Section: Introductionmentioning
confidence: 99%